Characterization for the necessity of thermophilic biogas digester of tea waste and cooked waste for biogas production - Nirmal Halder (International Journal of Advances in Applied Sciences, 2020)
Characterization of tea waste, cooked waste has been done by various authors but for the first time it has been done for understanding the necessity of thermophilic digestion. And for this kind of digestion takes place in thermophilic digester for efficient biogas production. Detailed morphological analysis of feedstock has been determined. In the present study, thermo gravimetric analysis carried out For easy and fast digestion of cooked waste, a novel design of thermophilic digester is proposed and tested.